The answer to the expression "1 7" is unclear as it is missing an operator (such as +, -, *, /) to indicate the mathematical operation being performed between the numbers. In mathematics, without an operator, it is difficult to determine the intended calculation. If you provide more context or specify the operation, I can give you the correct answer.
2 1/7 7/7 + 7/7 + 1/7 = 15/7 1 + 1 + 1/7 = 2 1/7
1/7 of 7 = 1
15/72 1/7:= [(7 * 2)+1]/7= [14 + 1]/7= 15/7 in improper fraction
7 - 1 = 66
It will depend on where you put your parentheses. Root 7 -( 1/root 7) is different from (root 7-1)/root 7. * * * * * True, but a more helpful answer: [sqrt(7) - 1]/[sqrt(7) + 1] - [sqrt(7) + 1]/[sqrt(7) - 1] Multiplying the numerator and denominator of the first fraction by [sqrt(7) - 1] and the second fraction by [sqrt(7) + 1] = [sqrt(7) - 1]2/[7 - 1] - [sqrt(7) + 1]2/[7 - 1] =[7 - 2*sqrt(7) + 1]/6 - [7 + 2*sqrt(7) + 1]/6 = 16/6 = 8/3
(1 + 1/7) = (7/7 + 1/7) = 8/7
2 1/7 7/7 + 7/7 + 1/7 = 15/7 1 + 1 + 1/7 = 2 1/7
7 ÷ 1/7 = 7 × 7/1 = 49.
It is 1/7. When you multiply (1/7) by 7 you get 1 as a result.
1/7 of 7 = 1
15/72 1/7:= [(7 * 2)+1]/7= [14 + 1]/7= 15/7 in improper fraction
Yes since 7+1 > 7 1+7 > 7 7+7 > 1 Those are all true. So Yes.
7*(7 + 7) + 7/7 + 7/7 = 7*14 + 1 + 1 = 98 + 1 + 1 = 100
7 - 1 = 66
It will depend on where you put your parentheses. Root 7 -( 1/root 7) is different from (root 7-1)/root 7. * * * * * True, but a more helpful answer: [sqrt(7) - 1]/[sqrt(7) + 1] - [sqrt(7) + 1]/[sqrt(7) - 1] Multiplying the numerator and denominator of the first fraction by [sqrt(7) - 1] and the second fraction by [sqrt(7) + 1] = [sqrt(7) - 1]2/[7 - 1] - [sqrt(7) + 1]2/[7 - 1] =[7 - 2*sqrt(7) + 1]/6 - [7 + 2*sqrt(7) + 1]/6 = 16/6 = 8/3
4 * 7/1 = 28 ---------( means there are 28 1/7's in 4 )
7